Return intentions of university-educated Turkish expatriates - Nil Demet Güngör; Aysit Tansel (Institute for the Study of Labor (IZA), 2005)
The study presents research findings on the return intentions of Turkish professionals residing abroad, where the targeted group comprises individuals working at a full time job abroad and possessing a tertiary-level degree. The data are obtained from an internet survey of Turkish professionals conducted by the authors during the first half of 2002. A total of 1224 usable responses were obtained from a combination of internet search and referral sampling methods. Student non-return appears to be more significant compared to professional migration, since participants with foreign degrees appear less likely to return. There is a strong, positive association between initial return intentions and current return intentions, although this weakens with the length of stay. The findings also tend to confirm that the recent economic crises in Turkey have had an adverse impact on the return intentions of university educated professionals working abroad.
Keywords: F20; F22; 330; skilled migration; brain drain; return intentions; higher education; Turkey